The Life and Most Surprising Adventures of Robinson Crusoe, of York, Mariner (1801) - Defoe, Daniel, 1661?-1731 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Life and Most Surprising Adventures of Robinson Crusoe, of York, Mariner" by Daniel Defoe is an adventure novel published in 1719. After ignoring his parents' wishes, Robinson Crusoe embarks on sea voyages that lead to disaster. Shipwrecked on a remote tropical island, he survives alone for 28 years, building shelter, growing crops, and reading the Bible. His solitary existence is disrupted when he discovers cannibals visiting the island. Eventually, he rescues a prisoner he names Friday, finding companionship and renewed hope for escape. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Robinson_Crusoe
Release date is 2004-04-01
E-text prepared by Internet Archive; University of Florida; and Charlie Kirschner
Keywords: Shipwreck survival -- Fiction; Islands -- Fiction; Crusoe, Robinson (Fictitious character) -- Fiction; Atlantic Ocean -- Fiction; Adventure stories; Castaways -- Fiction